Sei sulla pagina 1di 6

# A Note on the Irrationality of (3)

MANJIL P. SAIKIA1

## Work done as part of a summer programme in Chennai Mathematical Institute under

Dr. Purusottam Rath.

## Key Words: Zeta functions, Aperys constant.

1. Introduction
At the Journees Arithmetiques held at MarseilleLuminy in June 1978, Roger
Apery gave an elmentary proof of the irrationality of (3) = 113 + 213 + . . ..However
due to the complexity of the proof there was a general disagreement amongst the
mathematicians present there as to the validity of the proof presented. Two months
later a complete exposition of the proof was presented at the International Congress
of Mathematicians in Helsinki in August 1978 by H. Cohen. This proof was based on
the lecture by Apery but also contained some ideas of Cohen and Don Zaiger. Then
in 1979 F. Beukers gave a very simple proof of the result in . In this note we shall
give an account of the proof given by Beukers. Beukers proof uses some elementary
calculus involving few double and triple integrals.
2. Preliminaries
We prove in this section few non-trivial lemmas which shall be required in our proof
of the irrationality of (3).
log n
Lemma 2.1. The LCM of 1, 2, 3 . . . , n is denoted by dn , then dn = pn pb log p c <
Q
log n
log p = n(n) .
Q
pn p

Proof. If p1 , p2 , . . . , p(n) are all the prime numbers less than or equal to n. If p
is a prime bigger than n then p does not divide any of 1, 2, 3, . . . , n, so p doesnt
a(n)
divide dn . Thus dn = pa11 pa22 , p(n) for some ai s (i = 1, 2, 3, . . . , (n)). We
blogp nc blogp nc+1
have that p n and p > n hold for any prime less or equal than dn .
logn
blogp nc
|| dn . Thus ai = logpi n. Hence, dn = pn pblogp nc = pn pb logp c <
Q Q
So p
logn
logp n
= pn n = n(n) .
Q Q Q
pn p
logp =
pn p 
Lemma 2.2. n (n) < 3n .
(log 3)n
Proof. Accoring to the prime number theorem we have (n) < log n
for sufficiently
large n. So, n (n) < 3n . 
1Currently a Summer Fellow at Chennai Mathematical Institute, Siruseri, Chennai600103, India.
1
2 Manjil P. Saikia

## Lemma 2.3. Let r and s be non-negative integers. If r > s then,

R 1 R 1 xr y s
0 0 1xy dxdy is a rational number whose denominator is a divisor of d2r .
R 1 R 1 log xy r s
0 0 1xy x y dxdy is a rational number whose denominator is a divisor of
d3r .
If r = s, then
R 1 R 1 xr y r
0 0 1xy dxdy = (2) 112 212 . . . r12 .
R 1 R 1 log xy r r
0 0 1xy x y dxdy = 2{(3) 113 213 . . . r13 }.
1 1 1 1
When r = 0 we let the sums 12
+ ... + r2
and 13
+ ... + r3
vanish.
Proof. Let be any non-negative integer. We consider the integral,

1 1
xr+ y s+
Z Z
In = dxdy (2.1)
0 0 1 xy
It is very easy to see that when the denominator of the In is expressed as a Geometric
Series we get the following,
Z 1 Z
1X
In = (xy)k xr+ y s+ dxdy
0 0 k=0

Z
X 1 Z 1
k+r+
= ( x dx)( y k+s+ dy)
k=0 0 0

X 1 1
= ( . )
k=0
k+r++1 k+s=+1

X 1 1
= ( ) (2.2)
k+0
k+s++1 k+r++1
The above is true since r > s. So, finally we have,

1 1 1
In = ( + ... + ) (2.3)
rs s+1+ r+
If we put = 0 now then the first part of our lemma follows immediately.
Differentiating with respect to and putting = 0, In changes to ,
Z 1 Z 1
log xy r s
In = x y dxdy (2.4)
0 0 1 xy
And the summation becomes

1 1 1
( 2
+ ... + 2
r s (s + 1) r
This proves the second part of the lemma.
A Note on the Irrationality of (3) 3

## We now assume r = s, then it is easy to see that,

1 1
xr+ y r+
Z Z X 1
In = dxdy =
0 0 1 xy k=0
(k + r + + 1)2
By putting = 0 as before we get the third part of the lemma as follows,

1 1
In = 2
+ + ...
(r + 1) (r + 2)2
This equals,

1 1 1 1 1 1 1 1
( 2
+ 2 + ... + 2 + 2
+ 2
+ . . .) ( 2 + 2 + . . . + 2 )
1 2 r (r + 1) (r + 2) 1 2 r
Thus,

1 1 1
In = (2)
2
2 ... 2
1 2 r
Again, we differentiate with respect to and put = 0. Then,

1 1
2
Z Z
log xy r r X
In = x y dxdy =
0 0 1 xy k=0
(k + r + 1)3
The above equals to

1 1
2( 3
+ + . . .)
(r + 1) (r + 2)3
which in turn equals to

1 1 1 1 1 1 1
2(( + + . . . + + + . . .) ( + + . . . + ))
13 23 r3 (r + 1)3 13 23 r3
Thus,

1 1 1
In = 2((3)
3
3 ... 3)
1 2 r
which proves the final part of the lemma.

R1 1 log xy
Lemma 2.4. 0 1(1xy)z
dz = 1xy
.

## Proof. We substitute (1 xy)z = u in the integral which gives (1 xy)dz = du.

Changing the limits we get,
4 Manjil P. Saikia

Z 1 Z 1xy
1 1
dz = du
0 1 (1 xy)z 0 (1 u)(1 xy)
Z 1xy
1 1
= du
1 xy o 1u
1
= | log(1 u) |1xy
1
1 xy
log xy
=
1 xy

u(1u)v(1v)w(1w)
Lemma 2.5. If F (u, v, w) = 1(1uv)w
and u, v, w (o, 1) then
1
M ax F (u, v, w) .
27
Proof. We have
p
1 (1 uv)w = 1 w + uvw 2( (1 w) uvw)
So,
1p
F (u, v, w) (1 w)w u(1 u) v(1 v)
2
Again,

1 2 1
M ax0t1 t(1 t2 ) = . , t =
3 3 3
p 1 1 1
M ax0t1 t(1 t) = . , t =
2 2 2
So,

1 1 2 2 1
M ax [F (u, v, w)] . . . = .
2 2 3 3 3 3 27

3. Irrationality of (3)
Theorem 3.1. (3) is irrational.
Proof. We consider the integral,

1 1
log xy
Z Z
In = Pn (x)Pn (y)dxdy,
0 0 1 xy
d n n n 1
where Pn (r) = ( dr ) r (1 r) . n! . It is clear from Lemma 2.3 that for some An , Bn
Z we have,
A Note on the Irrationality of (3) 5

In = (An + Bn (3))d3
n (3.1)
Using Lemma 2.4 In changes into,
Z 1 Z 1 Z 1
Pn (x)Pn (y)
In = dxdydz
0 0 0 1 (1 xy)z
After partially integrating the above integral with respect to x n-times the interal
changes into,

1 1 1
(xyz)n (1 x)n Pn (y)
Z Z Z
In = dxdydz (3.2)
0 0 0 (1 (1 xy)z)n+1
1z
We now use the substitution w = 1(1xy)z
to get,
Z 1 Z 1 Z 1
Pn (y)
In = (1 x)n (1 w)n dxdydw
0 0 0 1 (1 xy)w
1 1 1
[x(1 x)y(1 y)w(1 w)]n
Z Z Z
= dxdydw (3.3)
0 0 0 [1 (1 xy)w]n+1
where the last equality again follows from an n-fold integration by parts with respect
to w like earlier.
From Lemma 2.5 and Lemma 2.4 it follows that the integral is bounded above by

1 1 1 1 1
log xy
Z Z Z Z Z
1 1 1
( )n dxdydw = ( )n dxdy
27 0 0 0 1 (1 xy)w 27 0 0 1 xy
1 n
The above is equal to 2( 27 ) (3)
by Lemma 2.3.
Since integral (3.3) is not zero, so we have

1 n
0 <| An + Bn (3) | d3
n < 2(3)( )
27
and hence by Lemma 2.1 and Lemma 2.2

1 n 4
0 <| An + Bn (3) |< 2(3)d3n (
) < 2(3) < ( )n (3.4)
27 5
for sufficiently large n, which proves the irrationality of (3).


4. Acknowledgements
The author wishes to thank Dr. P. Rath for his immense help and guidance and
Prof. F. Beukers for .
6 Manjil P. Saikia

References
 M. Aigner, G. M. Ziegler, Proofs from THE BOOK, Springer India, 2010.
 F. Beukers, A note on the Irrationality of (2) and (3), Bull. Lon. Math. Soc. 11 (1979), 268272.
 F. Beukers, Elementary Number Theory WISB321, Lecture Notes, 2009.
 J. M. Borwein, P. B. Borwein, Pi and the AGM: A Study in Analytic Number Theory and Com-
putational Complexity, WileyIntescience, 1998.